Analysis of Factors Related to the Implementation of Regional Regulation Number 08 of 2017 Concerning Non-Smoking Areas - Nurkholis Nurkholis; Ratno Adrianto; Irfansyah Baharuddin Pakki (Indonesian Journal of Global Health Research, 2025)
Smoking is a detrimental habit that contributes significantly to public health problems. To address this issue, the East Kutai Regency Government issued Regional Regulation Number 08 of 2017 concerning No-Smoking Areas. One of the designated KTR pillars is SMAN 2 North Sangatta, which plays a strategic role in reducing the high prevalence of smoking among adolescents. This study aims to analyze the influence of communication, resources, bureaucratic structure, and attitudes on the implementation of the KTR regulation. The research applied an analytical survey with a cross-sectional design involving 422 respondents from the academic community of SMAN 2 North Sangatta, selected through consecutive sampling. Data were collected through questionnaires and analyzed using chi-square and logistic regression tests. The findings revealed a significant relationship between communication and the implementation of the Smoke-Free Area regulation (p<0.001), as well as between resources and implementation (p<0.001). Conversely, bureaucratic structure showed no significant relationship (p=0.779)while attitudes demonstrated a positive influence. Logistic regression analysis confirmed that communication and resources were the most influential factors in ensuring effective implementation (p= 0.000<0.05). In conclusion, strengthening communication and optimizing resource allocation are essential to improving compliance with KTR policies in schools.